Identificação de micro-organismo isolado da rizosfera da macrófita fitorremediadora de lixiviado Alternanthera philoxeroides - Silva, Vanessa Leitner (2017)
Urban Solid Waste (USW) growth has become an economic, social and environmental concern in modern society. Concerning environmental issues, landfill disposal is considered the most appropriate destination, despite leachate formation. As its composition presents high organic and inorganic content, careless disposal greatly interferes with the environment, where conventional and complementary treatments may be employed for diminishing pollutant load. The inactive Curitiba’s Landfill (Curitiba, PR – Brazil) is composed of three natural wetlands where leachate treatment is performed with the aid of phytoremediation by the action on macrophytes, being Alternathera philoxeroides the dominant species. The present study aimed to identify and immobilize a microorganism isolated from A. philoxeroides rhizosphere, for pollutant degradation, in order to maximize treatment already performed in landfill. For that matter, morphological and molecular characterization of an isolated microorganism was performed through Gram staining and through molecular biology techniques, respectively, being identified the bioremediation bacteria. Next, initial assays attempted to evaluate leachate degradation related to biomass growth through fermentation in Erlenmeyer flasks under controlled agitation (shaker). As the bacteria presented potential in consuming leachate for its biomass growth, the assays were performed in bench bioreactors (5 L) in order to ensure maximum biomass growth, using leachate or enriched mineral medium as substrates, respectively. The measured parameters were as follows: hydrogenionic potential (pH), Dissolved Oxygen (DO), electrical conductivity, and Chemical Oxygen Demand (COD). The final biomass obtained were of 1,2 g.L-1 and 3,9 g.L-1 , using leachate and enriched mineral medium as substrates, respectively. The results indicate that the bacterium isolated from the rhizosphere of A. philoxeroides is tolerant to leachate and has potential to be used in bioremediation processes when the strategy used is biostimulation, since the presence of nutrients can positively influence its growth and in the rate of degradation of the leachate.